1988
DOI: 10.1111/j.1540-8159.1988.tb06308.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Capture Detection with Endocardial Electrodes

Abstract: A new method of evoked response detection, previously demonstrated in the ventricle, has been studied in the atrium at the time of routine pacemaker implant in 16 patients. The atrial evoked response was readily detectable in all patients due to excellent recovery from poststimulus polarization. In six patients, as experimental threshold-tracking pacemaker was used to automatically verify atrial capture and to generate strength-duration curves. It is concluded that this pacing technique is both simple and reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…When the stimulation pulse ends, the polarization begins a slow decay as the ions diffuse back to electrically neutral configurations 5 . Experiments by Livingston et al 8 indicate that polarization amplitude increases linearly with stimulus voltage.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…When the stimulation pulse ends, the polarization begins a slow decay as the ions diffuse back to electrically neutral configurations 5 . Experiments by Livingston et al 8 indicate that polarization amplitude increases linearly with stimulus voltage.…”
Section: Introductionmentioning
confidence: 98%
“…Various attempts have been made to minimize polarization. Livingston 8 and Feuer 9 noted that one can obtain a unipolar atrial evoked‐response signal from the ring electrode of a bipolar lead during unipolar pacing from the tip electrode. Kay et al 10,11 and Butter et al 12 reported identifying atrial capture using the voltage difference between the atrial ring electrode and the tip of the ventricular lead.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several methods to detect paced events that depolarize or capture the myocardium have been developed and applied to the various chambers of the heart. One such method evaluates changes in the evoked response (ER) signal characteristics to discriminate captured events from non‐captured events and to determine the threshold through identification of persistent loss of capture 14–31 . Use of the ER signal characteristics for the ACV algorithm poses design constraints due the relative size of the ER signal to the significantly larger pacing artifact that remains on the lead‐tissue interface after a paced event.…”
Section: Introductionmentioning
confidence: 99%
“…One such method evaluates changes in the evoked response (ER) signal characteristics to discriminate captured events from non-captured events and to determine the threshold through identification of persistent loss of capture. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] Use of the ER signal characteristics for the ACV algorithm poses design constraints due the relative size of the ER signal to the significantly larger pacing artifact that remains on the lead-tissue interface after a paced event. Several technological approaches have been developed in an attempt to eliminate the influence of the pacing artifact and to improve capture discrimination using the ER.…”
mentioning
confidence: 99%